2018
DOI: 10.1253/circj.cj-17-1242
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Chronic Thromboembolic Pulmonary Hypertension at a Single Japanese Pulmonary Endarterectomy Center

Abstract: Survival in CTEPH in the recent era has significantly improved, especially in non-PEA patients. BPA and selective pulmonary vasodilators could improve survival in the non-PEA group. In the present study, no difference in survival was found between PEA and non-PEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 22 publications
2
19
6
1
Order By: Relevance
“…22 Our group has recently identified that a Jamieson classification of III or IV and a high PVR were associated with poor survival, although similar survival rates were recently observed in patients with CTEPH treated by BPA, PEA, and medication between 2009 and 2016. 23 The findings of the present study are similar in that a Jamieson classification of III or IV was a poor prognostic factor, providing evidence that having a PD may be an additional important risk factor for perioperative death in patients with CTEPH.…”
Section: Discussionsupporting
confidence: 80%
“…22 Our group has recently identified that a Jamieson classification of III or IV and a high PVR were associated with poor survival, although similar survival rates were recently observed in patients with CTEPH treated by BPA, PEA, and medication between 2009 and 2016. 23 The findings of the present study are similar in that a Jamieson classification of III or IV was a poor prognostic factor, providing evidence that having a PD may be an additional important risk factor for perioperative death in patients with CTEPH.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, a recent study showed that even though in patients treated before 2008 PEA enabled significantly better survival than medication, in a group of CTEPH patients who initiated treatment in 2009–2016, no difference in survival between PEA, BPA and medication was observed. 33 With recent cases of patients treated with both PEA and BPA, 34,35 it has been suggested that in the future some patients may benefit most from various combinations of surgical therapy, percutaneous therapy and MT. 5…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic PAH (IPAH) patients admitted for RHC were also enrolled for a comparison during the same period. The definition of CTEPH was described previously ( 10 ). IPAH was defined as follows: ( 1 ) a mean pulmonary arterial pressure (mPAP) of ≥25 mmHg and normal pulmonary arterial wedge pressure (PAWP) on RHC; ( 2 ) no perfusion defect on lung scintigraphy; and ( 3 ) no identifiable cause of pulmonary hypertension (connective tissue disease, congenital heart disease, portal hypertension, HIV infection, chronic lung disease) on further diagnostic work-up.…”
Section: Methodsmentioning
confidence: 99%
“…Idiopathic PAH (IPAH) patients admitted for RHC were also enrolled for a comparison during the same period. The definition of CTEPH was described previously (10). IPAH was defined as follows: (1) a mean pulmonary arterial pressure (mPAP) of !…”
Section: Study Populationmentioning
confidence: 99%